Monotonic tests of structural carpentry joints - Palma, P. (2010)
An experimental campaign on traditional diagonal front notched timber joints was carried out in order to assess their rotational behaviour. This campaign included ten different test conditions, comprising some of the most frequently observed configurations of the rafter and tie beam joint in Portuguese roof structures. The joints' mechanical behaviour was appraised with regard to their geometric parameters, presence of metal fastening devices and moisture content of timber. The experimental results show that the joint's response is different when opening or closing the skew angle and that specific load bearing mechanisms dictate the different performances exhibited by each typology.